Picumã: performace drag queen em uma epistemologia decolonial - Bezerra, Pedro Henrique Almeida (2018)
The drag queen practice has a suitability process that shifts a person's unexceptional appearance to a different appearance that can transit between the genres (male, female, polymorph) and species (animal representations). The present work aims to observe the practice in the city of Fortaleza - CE with the intention of absorbing its processes of creation, adaptation, “be in drag” and “out of drag”. Understand how mutations are the practices that are subject to external influences and the adaptability of the queens studied. Using analytical lenses that make it possible to see the practices of a performance epistemology that leads to the decolonization of thought and a concern of scientific criticism, the study is based on an ethnographic experience based on the dense description and on-the-spot interviews. Used as log the field diary, photos, videos and voice recorder. It was concluded that a drag queen in the city of Fortaleza - CE passed and underwent constant changes with respect to the tradition and the emergence of new ways to make drag which are impacted by the RuPaul’s Drag Race reality show and its tendency to turn the queen into a product that can be marketed worldwide through TV. It was also observed that in addition to the strong influence brought about by this reality show, the local context has been resistant the attempts of supplanting the tradition having as elements of resistance the "bate-cabelo" and the dialect "yorubá" that refer to a force history of oppression: colonization.